Pregnancy outcome following first-trimester exposure to fingolimod: A collaborative ENTIS study. (March 2021) - Pauliat, Emmanuelle; Onken, Marlies; Weber-Schoendorfer, Corinna; Rousson, Valentin; Addor, Marie-Claude; Baud, David; Théaudin, Marie; Diav-Citrin, Orna; Cottin, Judith; Agusti, Antonia; Rollason, Victoria; Kaplan, Yusuf C; et al.
This prospective multicentre cohort study investigated pregnancy outcomes after fingolimod use for multiple sclerosis during pregnancy. Pregnancy outcomes of 63 fingolimod and 62 interferon-β-exposed pregnancies were compared. Rates of major congenital anomalies (MCA) were 4.8% (2/42) in the fingolimod group versus 2.3% (1/44) in the interferon-β group (odds ratio, 2.2; 95% confidence interval, 0.2–24.6). The adjusted hazard ratio for spontaneous abortion in fingolimod versus interferon-β-exposed pregnancies was 0.6 (95% confidence interval, 0.2–1.8). Further studies are needed to definitely rule out a moderately increased MCA risk after fingolimod exposure during pregnancy.